Modeling and Simulation of Biomechanical Systems - An Orbital Cavity, a Pelvic Bone and Coupled DNA Bases - Awrejcewicz, J.; Mrozowski, J.; Młynarska, S.; Dąbrowska-Wosiak, A.; Zagrodny, B.; Banasiak, S.; Yakushevich, L.V. (IntechOpen, 2011)
None